A lentiviral vector bearing a reverse intron demonstrates superior expression of both proteins and microRNAs. Issue 11 (2nd November 2017) - Poling, Brigid Chiyoko; Tsai, Kevin; Kang, Dong; Ren, Linda; Kennedy, Edward M.; Cullen, Bryan R.
ABSTRACT: While lentiviral expression vectors are widely used in many facets of molecular biology, due to their ability to stably express heterologous genes in both dividing and non-dividing cells, they suffer from the disadvantage that introns inserted into the vector genome are generally rapidly lost by splicing in packaging cell lines. The presence of an intron, if achievable, has the potential to facilitate the expression of transgene cDNAs, as splicing has been extensively shown to facilitate mRNA biogenesis and function. Moreover, if a stable intron could be introduced into a lentiviral vector, this could greatly facilitate the expression of microRNAs (miRNAs), and especially miRNA clusters, as the introduction of pri-miRNA stems into the exonic region of a lentiviral vector can strongly reduce both vector titer and the expression of any miRNA-linked indicator gene due to cleavage of the vector RNA genome by cellular Drosha. Here, we describe a novel lentiviral vector design in which transgenes and/or miRNAs are expressed using an antisense-orientated, inducible promoter driving an expression cassette bearing a functional intron. We demonstrate that this lentiviral vector, called pTREX, is able to express higher levels of both transgenes and pri-miRNA clusters when compared with a closely similar conventional lentiviral vector.